PILOT PROYEK PEMBANGKIT LISTRIK TENAGA BIOGAS SKALA RUMAH TANGGA - Nindhia, T.G.T.; Surata, I.W.; Nindhia, T.S.; Swastika, I.D.G.P. (Buletin Udayana Mengabdi; Vol 20 No 1 (2021): Buletin Udayana MengabdiDO - 10.24843/BUM.2021.v20.i01.p14, 2021)
Buahan Village, Payangan District in Gianyar Regency, Bali is an agricultural village with most of its inhabitants as farmers and ranchers. Livestock, especially cattle and pigs are widely available in this area and very potential to be developed as a source of energy reserves especially biogas obtained from the processing of farm waste through anaerobic digester. Biogas is commonly used for cooking but the use of further biogas for biogas power plants needs to be developed and disseminated. This is due to the decreasing availability of conventional energy which causes the price of electricity continues to increase. This dedication aims to build a pilot biogas power plant project to introduce and disseminate affordable and cost-effective technology of household-scale biogas power plant in Buahan Village, Payangan District, Gianyar, Bali. Furthermore, this activity succeeds to create a biogas power plant with a capacity of 1000 watts with biogas fuel and has been installed with a well equipped house generator. The study also produced a double stove biogas stove for cooking using biogas.